Laminate and method for producing laminate
By designing a first resin layer with a storage portion and a first conductive layer arranged therein in the laminate, an amorphous thermoplastic resin is used between the conductive layer and the insulating layer, and between the insulating layer and the second conductive layer, by using an amorphous thermoplastic resin between the conductive layer and the insulating layer and between the insulating layer and the second conductive layer. As the main component adhesive layer, the problem of insufficient thermal durability of the laminated body in a high temperature environment is solved, and higher thermal stability is achieved.
Patent Information
- Application Number
- CN202380050922.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-12-23
- Filing Date
- 2023-11-15
- Publication Date
- 2025-02-14
AI Technical Summary
The existing laminates have insufficient thermal durability in high temperature environments, resulting in internal stresses of the conductive layer and the resin layer, resulting in cracks and deformation.
A laminated body structure is adopted, wherein the first resin layer has a storage portion, the first conductive layer is arranged in the storage portion, and an adhesive layer is arranged between the conductive layer and the insulating layer, and between the insulating layer and the second conductive layer. The adhesive layer is composed of amorphous thermoplastic resin.
With this structural design, internal stress generated during heating can be alleviated, cracks can be generated and deformation between the conductive layer and the resin layer can be suppressed, and the thermal durability of the laminate can be significantly improved.
Smart Images

Figure CN119451818A_ABST
Abstract
Description
Technical Field
[0001] The present disclosure relates to a laminate and a method for producing the laminate. Background Art
[0002] A power module (PM) mounted in a hybrid vehicle or the like includes a laminate (also referred to as a casing) of a resin molded article and a metal.
[0003] Conventionally, the housing is manufactured by placing a conductive layer and an insulating layer in a mold, injecting a resin into the mold, and performing molding (hereinafter also referred to as insert molding) (see Patent Document 1).
[0004] Prior art literature
[0005] Patent Literature
[0006] Patent Document 1: Japanese Patent Application Publication No. 2021-122959 Summary of the invention
[0007] Problems to be solved by the invention
[0008] Generally, a heat sink to which components etc. are brazed is bonded to a housing used in a PM.
[0009] From the viewpoint of improving manufacturing efficiency, it is desirable to bond the heat sink to the housing at the same time as bonding the components to the heat sink. However, by brazing the components to the heat sink, heat is applied to the housing.
[0010] This time, the inventors have discovered that the conventional housing manufactured by insert molding disclosed in Patent Document 1 has a conductive layer buried in a resin layer. Therefore, when the laminate is left standing in a high-temperature environment or heated, the internal stress generated by the difference in linear expansion coefficients between the conductive layer and the resin layer cannot be fully alleviated, resulting in cracks and deformation of the conductive layer and the resin layer, and its thermal durability has room for improvement.
[0011] An object of one embodiment of the present disclosure is to provide a laminate having excellent thermal durability and a method for producing the laminate.
[0012] Means for solving problems
[0013] <1> A laminate comprising:
[0014] 1st resin layer,
[0015] The first conductive layer,
[0016] Insulation layer, and
[0017] The second conductive layer,
[0018] The first resin layer has a receiving portion.
[0019] The first conductive layer is disposed in the housing portion of the first resin layer.
[0020] An adhesive layer is provided between at least one of the first conductive layer and the insulating layer and between the insulating layer and the second conductive layer, the adhesive layer comprising a solid binder having an amorphous thermoplastic resin as a main component, the amorphous thermoplastic resin being at least one selected from a thermoplastic epoxy resin and a phenoxy resin, the epoxy equivalent of the amorphous thermoplastic resin being 1,600 or more or the amorphous thermoplastic resin containing no epoxy group,
[0021] The amorphous thermoplastic resin has a heat of fusion of 15 J / g or less.
[0022] <2> The laminate according to <1> above, wherein the housing portion includes a concave portion or a concavo-convex portion.
[0023] <3> The laminate according to <1>, wherein the first conductive layer, the insulating layer, and the second conductive layer are arranged in the housing portion of the first resin layer.
[0024] <4> In the laminate according to <1> or <2>, an area of the housing portion of the first resin layer is equal to or larger than an area of the first conductive layer.
[0025] <5> The laminate according to any one of <1> to <4>, further comprising a second resin layer on the side of the second conductive layer opposite to the insulating layer,
[0026] The adhesive layer is optionally provided between at least one of the first resin layer and the first conductive layer and between the second conductive layer and the second resin layer.
[0027] <6> The laminate according to any one of <1> to <5>, wherein the first resin layer is a cured product of a resin composition containing a thermosetting resin.
[0028] <7> The laminate according to <6>, wherein the thermosetting resin includes an unsaturated polyester.
[0029] <8> The laminate according to any one of <1> to <7>, wherein the first resin layer has a fixing portion that fixes the first conductive layer, the insulating layer, and the second conductive layer.
[0030] <9> A method for producing a laminate, comprising the following steps:
[0031] a pre-bonding step of preparing a laminated body in which a first resin layer having a receiving portion, a first conductive layer disposed in the receiving portion of the first resin layer, an insulating layer, and a second conductive layer are sequentially disposed, and a solid bonding agent is disposed at least one between the first conductive layer and the insulating layer and between the insulating layer and the second conductive layer, wherein the solid bonding agent contains an amorphous thermoplastic resin as a main component, and the amorphous thermoplastic resin is at least one selected from a thermoplastic epoxy resin and a phenoxy resin; and
[0032] a bonding step of heating and pressurizing the laminate to melt the solid bonding agent, bonding the first conductive layer to the insulating layer and / or bonding the insulating layer to the second conductive layer,
[0033] The epoxy equivalent of the amorphous thermoplastic resin is 1,600 or more or the amorphous thermoplastic resin does not contain an epoxy group,
[0034] The amorphous thermoplastic resin has a heat of fusion of 15 J / g or less.
[0035] <10> The method for producing a laminate according to <9>, wherein the heating and pressurizing are performed under the conditions of 100° C. to 400° C. and 0.01 MPa to 20 MPa.
[0036] <11> The method for producing a laminate according to <9> or <10>, wherein the solid adhesive before melting has any shape selected from the group consisting of a film, a rod, particles, and a powder.
[0037] Effects of the Invention
[0038] According to one embodiment of the present disclosure, a laminate having excellent thermal durability and a method for producing the laminate can be provided. BRIEF DESCRIPTION OF THE DRAWINGS
[0039] Figure 1 This is a perspective view showing one embodiment of the laminated body disclosed herein.
[0040] Figure 2 It is a perspective view showing another embodiment of the laminated body disclosed in the present invention.
[0041] Figure 3 This is a perspective view showing one embodiment of the laminated body disclosed herein.
[0042] Figure 4 It is a cross-sectional view showing another embodiment of the laminated body disclosed in the present invention.
[0043] Figure 5 It is a cross-sectional view showing another embodiment of the laminated body disclosed in the present invention.
[0044] Figure 6 This is a perspective view showing one embodiment of the first resin layer included in the laminate of the present disclosure.
[0045] Figure 7 This is a perspective view showing one embodiment of the first resin layer included in the laminate of the present disclosure.
[0046] Figure 8 It is a perspective view showing another embodiment of the laminated body disclosed in the present invention.
[0047] Fig. 9 It is a schematic cross-sectional view showing a state in which a first member and a second member are bonded together via an adhesive layer containing a solid bonding agent. DETAILED DESCRIPTION
[0048] Hereinafter, the method for implementing the present disclosure is described in detail. However, the present disclosure is not limited to the following embodiments. In the following embodiments, its constituent elements (including element steps, etc.) are not necessary except for the cases specifically described. The same is true for numerical values and their ranges, which do not limit the present disclosure.
[0049] In the present disclosure, the term "process" includes processes that are independent of other processes and processes that cannot be clearly distinguished from other processes as long as the purpose of the process is achieved. In the present disclosure, in the numerical range expressed by "to", the numerical values before and after "to" are included as the minimum value and the maximum value, respectively.
[0050] In the numerical ranges described in stages in the present disclosure, the upper limit value or the lower limit value described in one numerical range may be replaced with the upper limit value or the lower limit value of the numerical range described in another stage.
[0051] In addition, in the numerical range described in the present disclosure, the upper limit value or the lower limit value of the numerical range may be replaced with the value shown in the Examples.
[0052] In the present disclosure, each component may include a plurality of corresponding substances. When a plurality of substances corresponding to each component are present in the composition, the content rate or content of each component refers to the total content rate or content of the plurality of substances present in the composition unless otherwise specified.
[0053] In the present disclosure, the term "layer" includes a case where the layer is formed in the entire region and a case where the layer is formed only in a part of the region when observing the region where the layer exists.
[0054] In the present disclosure, when an embodiment is described with reference to the drawings, the configuration of the embodiment is not limited to the configuration shown in the drawings. In addition, the sizes of components in each figure are conceptual, and the relative relationship between the sizes of the components is not limited to this.
[0055] In the present disclosure, the term "joining" refers to connecting objects to each other, and bonding and welding are subordinate concepts thereof. Bonding refers to the joining of two adhered materials (substances to be bonded) via organic materials (curable resins, thermoplastic resins, etc.) such as tapes and adhesives. Welding refers to melting the surface of a thermoplastic resin or the like by heat, and bonding is performed by utilizing entanglement and crystallization caused by molecular diffusion during contact pressurization and cooling, or by molecular interactions with the substrate during melting.
[0056] [Laminate]
[0057] The laminated body of the present disclosure includes a first resin layer, a first conductive layer, an insulating layer, and a second conductive layer in this order. The first resin layer has a housing portion, and the first conductive layer is disposed in the housing portion of the first resin layer.
[0058] The laminate of the present disclosure is excellent in thermal durability. The reason why the above effect is achieved is not clear, but is presumed as follows.
[0059] The laminated body disclosed in the present invention can be manufactured by laminating each layer separately instead of insert molding. Therefore, in the laminated body manufactured by insert molding, the first conductive layer is buried in the first resin layer and is completely in close contact with it. In contrast, in the laminated body disclosed in the present invention, since the first resin layer has a receiving portion, it is not completely in close contact with the first conductive layer, and the internal stress generated during heating can be alleviated. It is inferred that the generation of cracks and the deformation of the conductive layer and the resin layer can be suppressed, and the thermal durability is improved.
[0060] Furthermore, the first resin layer has the housing portion, but it is difficult to form it by insert molding, and it is presumed that this improves the thermal durability.
[0061] The laminated body of the present disclosure may further include a second resin layer on the side of the second conductive layer opposite to the insulating layer.
[0062] The laminated body disclosed in the present invention has an adhesive layer between at least one of the first conductive layer and the insulating layer and between the insulating layer and the second conductive layer, and may further optionally have an adhesive layer between at least one of the first resin layer and the first conductive layer and between the second conductive layer and the second resin layer.
[0063] From the viewpoint of thermal durability, the adhesive layer is preferably disposed within the housing portion of the first resin layer.
[0064] The laminated body of the present disclosure may include a heat sink on the first resin layer side surface of the first conductive layer or the second resin layer side surface of the second conductive layer.
[0065] From the viewpoint of thermal durability, the heat dissipation plate is preferably disposed in the housing portion of the first resin layer.
[0066] (1st resin layer)
[0067] The first resin layer has a housing portion, and the first conductive layer is disposed in the housing portion.
[0068] From the viewpoint of thermal durability, the housing portion preferably includes a concave portion or a concavo-convex portion.
[0069] The so-called receiving portion includes a concave-convex portion means that the receiving portion includes a concave portion and a convex portion. The concave portion may be in a step shape.
[0070] From the viewpoint of thermal durability, the first conductive layer, the insulating layer, and the second conductive layer are preferably arranged in the housing portion of the first resin layer.
[0071] When the housing portion includes a stepped recessed portion, the first conductive layer, the insulating layer, and the second conductive layer may be housed in the same layer or in different layers.
[0072] exist Figure 3 to Figure 5 In FIG. 1 , a scheme in which the first conductive layer, the insulating layer, and the second conductive layer are accommodated in different levels of the stepped recessed portion is shown.
[0073] In addition, the first resin layer may have one housing portion, or may have two or more housing portions.
[0074] Figure 6 The first resin layer 100 shown has a plurality of housing portions 101 .
[0075] Figure 6 Each housing portion 101 included in the illustrated first resin layer 100 includes a concave portion 102A and a convex portion 102B.
[0076] When the first resin layer has a plurality of receiving portions, Figure 7 Although the first conductive layer 105 is disposed in a part of the housing portions as shown, the first conductive layer 105 may be disposed in all the housing portions.
[0077] In addition, the insulating layer and the second conductive layer do not need to be stacked on the first conductive layer arranged in all the receiving portions, and may be stacked as shown in FIG. Figure 8 As shown in FIG. 1 , the first conductive layer is stacked on all the first conductive layers arranged in the receiving portion. Figure 8 In the figure, the insulating layer is not shown, and the second conductive layer is indicated by the reference numeral 106.
[0078] The area of the receiving portion of the first resin layer is preferably greater than the area of the first conductive layer. The ratio of the area of the receiving portion of the first resin layer to the area of the first conductive layer (the area of the receiving portion of the first resin layer / the area of the first conductive layer) is preferably greater than 1.01. Thus, the first conductive layer can be easily arranged on the receiving portion of the first resin layer. In addition, the area ratio is preferably less than 2.00. Thus, there is a tendency to suppress the positional displacement of the first conductive layer on the first resin layer.
[0079] When the first resin layer has a receiving portion, its size is preferably appropriately changed according to the size of the first conductive layer, the purpose of the laminate, etc. The area of the receiving portion can be, for example, 1 cm 2 ~1000cm 2 .
[0080] The depth of the housing portion is preferably at least the thickness of the first conductive layer, more preferably the sum of the thicknesses of the first conductive layer, the insulating layer, and the second conductive layer, further preferably the sum of the thicknesses of the first conductive layer, the insulating layer, the second conductive layer, and the adhesive layer, and particularly preferably the sum of the thicknesses of the first conductive layer, the insulating layer, the second conductive layer, the adhesive layer, and the heat sink. The thickness of the housing portion may be, for example, 0.1 mm to 100 mm.
[0081] In addition, the depth of the housing portion may be smaller than the total thickness of the first conductive layer, the insulating layer, the second conductive layer, the adhesive layer, and the heat dissipation plate.
[0082] From the viewpoint of thermal durability, the first resin layer is preferably a cured product of a resin composition containing a thermosetting resin.
[0083] The type of thermosetting resin is not particularly limited, as long as it is a resin having one or more functional groups that can be used for a cross-linking reaction by heating in one molecule. Examples of the functional group include epoxy, acryloyl, methacryloyl, hydroxyl, vinyl, carboxyl, amino, maleimide, anhydride, thiol, sulfinyl, amide, and imide groups.
[0084] Examples of the thermosetting resin include phenolic resins, unsaturated imide resins, cyanate resins, isocyanate resins, benzoic acid resins, Oxazine resin, oxetane resin, amino resin, unsaturated polyester resin, acrylic resin, dicyclopentadiene resin, silicone resin, triazine resin, melamine resin, resorcinol resin, epoxy resin, etc. Among the above, from the viewpoint of thermal durability, it is preferred to contain one or more selected from unsaturated polyester and phenolic resin, and more preferably to contain unsaturated polyester.
[0085] The resin composition may contain one type of thermosetting resin alone, or may contain two or more types.
[0086] Unsaturated polyester can be obtained by polycondensing (esterifying) a polyol with an unsaturated polybasic acid, a saturated polybasic acid, or the like.
[0087] The polyol is not particularly limited, and conventionally known materials can be used. As the polyol, ethylene glycol, propylene glycol, butylene glycol, diethylene glycol, dipropylene glycol, triethylene glycol, pentylene glycol, hexylene glycol, neopentyl glycol, hydrogenated bisphenol A, bisphenol A, glycerol, etc. can be mentioned. They can be used alone or in combination of two or more.
[0088] The unsaturated polyacid is not particularly limited, and conventionally known substances can be used. Examples of the unsaturated polyacid include maleic anhydride, fumaric acid, citraconic acid, itaconic acid, etc. These can be used alone or in combination.
[0089] As saturated polyacid, there is no particular limitation, and known substances can be used. As saturated polyacid, phthalic anhydride, isophthalic acid, terephthalic acid, chlorobridgeic acid, succinic acid, adipic acid, sebacic acid, tetrachlorophthalic anhydride, tetrabromophthalic anhydride, endomethylenetetrahydrophthalic anhydride etc. can be enumerated. They can be used alone as one, or two or more can be used in combination.
[0090] As the unsaturated polyester, those synthesized by a known method using the above-mentioned raw materials may be used, or commercially available ones may be used.
[0091] Unsaturated polyester can be obtained by polycondensing a polyol with an unsaturated polybasic acid, a saturated polybasic acid, or the like in an inert gas atmosphere such as nitrogen at a temperature of 140° C. to 230° C. The polycondensation reaction can be carried out under pressure or under reduced pressure.
[0092] In the polycondensation reaction, a crosslinking agent or a catalyst may be used as necessary.
[0093] Examples of the crosslinking agent include styrene monomers, diallyl phthalate monomers, diallyl phthalate prepolymers, methyl methacrylate, triallyl isocyanurate, etc. These may be used alone or in combination of two or more.
[0094] Examples of the catalyst include manganese acetate, dibutyltin oxide, stannous oxalate, zinc acetate, cobalt acetate, etc. These may be used alone or in combination of two or more.
[0095] From the viewpoint of thermal durability, the number average molecular weight of the thermosetting resin is preferably 1,000 to 10,000, more preferably 1,500 to 5,000.
[0096] In the present disclosure, the number average molecular weight is a polystyrene-equivalent weight average molecular weight measured by gel permeation chromatography (GPC).
[0097] From the viewpoint of thermal durability, the content of the thermosetting resin relative to the total mass of the resin composition is preferably 10 to 60 mass %, more preferably 20 to 50 mass %, and even more preferably 20 to 40 mass %.
[0098] The resin composition may contain a thermoplastic resin, an elastomer, and the like.
[0099] Specific examples of thermoplastic resins include polyimide resins, polyamideimide resins, polyamide resins, polyetherimide resins, polybenzoic acid resins, Polyvinyl chloride resin, polyvinylidene chloride resin, polycarbonate resin, (meth) acrylic resin, polyester resin, polyacetal resin, polyphenylene sulfide resin (PPS), etc.
[0100] Specific examples of the elastomer include silicone rubber, styrene-butadiene rubber (SBR), nitrile rubber (NBR), and urethane rubber.
[0101] The resin composition may contain various additives such as curing agent, curing accelerator, filler, release agent, flame retardant, colorant, plasticizer, silane coupling agent, rust inhibitor, copper corrosion inhibitor, reducing agent, antioxidant, tackifying resin, ultraviolet absorber, defoaming agent, leveling regulator, solvent, etc.
[0102] The first resin layer may have a fixing portion for fixing the first conductive layer, the insulating layer, and the second conductive layer. The first resin layer has the fixing portion, so that the first conductive layer, the insulating layer, and the second conductive layer on the first resin layer tend to be prevented from being misaligned.
[0103] The first resin layer and the second resin layer may have either an insertion portion or an opening portion.
[0104] When the first resin layer has either one of the insertion portion and the opening portion and the second resin layer has at least the other, the first resin layer and the second resin layer can be fitted together by inserting the insertion portion into the opening portion.
[0105] (1st conductive layer and 2nd conductive layer)
[0106] The first conductive layer and the second conductive layer may include at least one of a metal and a metal oxide.
[0107] Examples of the metal include silver, gold, copper, palladium, platinum, titanium, chromium, nickel, aluminum, zirconium, tungsten, vanadium, rhodium, iridium, and alloys thereof.
[0108] Examples of the metal oxide include zinc oxide (ZnO), tin oxide (SnO 2 ), indium tin oxide (ITO), aluminum oxide (Al 2 O 3 ), and titanium oxide (TiO 2 ).
[0109] From the viewpoint of conductivity, the average thickness of the first conductive layer and the second conductive layer can be appropriately set according to the application, etc. Considering the ease of arrangement of the concave or concavo-convex portions of the first resin layer, the average thickness is preferably 0.1 mm to 10 mm.
[0110] In the present disclosure, the average thickness is determined by measuring the thickness at two points of a layer with a measuring instrument and taking the average value thereof.
[0111] The materials included in the first conductive layer and the second conductive layer, the average thickness of the layers, etc. may be the same or different.
[0112] (Insulation layer)
[0113] The insulating layer is preferably a cured product of a resin composition containing an insulating resin.
[0114] Examples of the insulating resin include curable resins such as thermoplastic resins, thermosetting resins, and photocurable resins.
[0115] As the photocurable resin, any resin having one or more unsaturated bonds that undergo crosslinking reaction by light in one molecule may be used. Specific examples of the photocurable resin include acrylic resins, urethane resins, polyester resins, polyether resins, epoxy resins, polybutadiene resins, polyimide resins, polyamide resins, silicone resins, fluororesins, and the like.
[0116] Since the thermoplastic resin and the thermosetting resin have been described above, their description is omitted here.
[0117] The resin composition may contain various additives such as a curing agent, a curing accelerator, a photopolymerization initiator, a filler, a release agent, a flame retardant, a colorant, a plasticizer, a silane coupling agent, a rust inhibitor, a copper corrosion inhibitor, a reducing agent, an antioxidant, a tackifying resin, an ultraviolet absorber, a defoaming agent, a leveling agent, a solvent, and the like.
[0118] From the viewpoint of insulation, the average thickness of the insulating layer can be appropriately set according to the application, etc. In consideration of the ease of arrangement of the concave portions or the concavo-convex portions of the first resin layer, the average thickness is preferably 0.01 mm to 10 mm.
[0119] (Second resin layer)
[0120] The laminated body of the present disclosure may further include a second resin layer on the opposite side of the second conductive layer from the insulating layer. By including the second resin layer, positional displacement of the first conductive layer, the insulating layer, and the second conductive layer on the first resin layer can be suppressed.
[0121] The second resin layer may have a concave portion, a convex portion, or a concavo-convex portion. The concave portion, the convex portion, or the concavo-convex portion provided in the second resin layer may be provided corresponding to the shape of the second conductive layer. The concave portion of the second resin layer corresponds to the shape of the second conductive layer, so that the position of the second conductive layer can be fixed by the second resin layer.
[0122] For example, when the total thickness of the first conductive layer, the insulating layer, and the second conductive layer is greater than the depth of the concave portion of the first resin layer, a concave portion matching the shape of the second conductive layer may be provided in the second resin layer. In this case, the area of the concave portion of the second resin layer is preferably greater than the area of the second conductive layer.
[0123] In addition, when the total thickness of the first conductive layer, the insulating layer, and the second conductive layer is smaller than the depth of the recessed portion of the first resin layer, a convex portion may be provided in the second resin layer at a position corresponding to the second conductive layer. The convex portion may be one or more than two.
[0124] The second resin layer is preferably a cured product of a resin composition containing a thermosetting resin. Since the thermosetting resin and the resin composition have been described above, their description is omitted here.
[0125] The second resin layer may have a fixing portion for fixing the first conductive layer, the insulating layer, and the second conductive layer. The second resin layer has the fixing portion, so that the first conductive layer, the insulating layer, and the second conductive layer on the first resin layer tend to be prevented from being misaligned.
[0126] (Adhesive layer)
[0127] The laminated body of the present disclosure includes an adhesive layer at least one of between the first conductive layer and the insulating layer, between the insulating layer and the second conductive layer, between the first resin layer and the first conductive layer, and between the second conductive layer and the second resin layer.
[0128] The first resin layer and the second resin layer can be bonded together by adjusting the size of the adhesive layer provided between any of the layers.
[0129] The adhesive layer may include an intermediate layer of an insulator. In this case, it is preferred that the adhesive layer is composed of three layers: a bonding material, an intermediate layer, and a bonding material from the viewpoint of adhesion and insulation. By including an intermediate layer of an insulator, defects such as insulating pinholes are less likely to form, and insulation can be improved.
[0130] Examples of the resin of the intermediate layer include polyimide resins, polyamideimide resins, polyamide resins, polyetherimide resins, polybenzoic acid resins, Polyvinyl chloride resin, polyvinylidene chloride resin, polycarbonate resin, (meth) acrylic resin, polyester resin, polyacetal resin, polyphenylene sulfide resin (PPS), phenolic resin, etc.
[0131] The adhesive layer contains a solid binder. Thus, when the first conductive layer, the adhesive layer, the insulating layer, etc. are laminated on the surface of the first resin layer, the thickness change of the adhesive layer can be suppressed, and the distance between the first conductive layer and the insulating layer, the distance between the first conductive layer and the second conductive layer, and the distance between the second conductive layer and the insulating layer can be suppressed.
[0132] (Solid cement)
[0133] The solid adhesive contains an amorphous thermoplastic resin as a main component, the amorphous thermoplastic resin is at least one selected from thermoplastic epoxy resins and phenoxy resins, the epoxy equivalent of the amorphous thermoplastic resin is greater than or equal to 1,600, or the amorphous thermoplastic resin does not contain an epoxy group, and the heat of fusion of the amorphous thermoplastic resin is less than or equal to 15 J / g.
[0134] The solid adhesive is solid at room temperature, that is, has no fluidity at 23° C. without pressure. The solid adhesive is preferably capable of maintaining its shape without deformation for more than 30 days at 23° C. without pressure, and further has the property of not deteriorating.
[0135] The above-mentioned "main component" refers to a component having the highest content among the resin components in the solid adhesive and a component having a content of 50% by mass or more in the resin components in the solid adhesive. The solid adhesive preferably contains 50% by mass or more of the resin component, more preferably 70% by mass or more, further preferably 80% by mass or more, and particularly preferably 90% by mass or more.
[0136] The so-called amorphous resin in the present disclosure is a resin that has a melting point (Tm) but does not have a clear endothermic peak associated with melting or has a very small endothermic peak in the measurement using a differential scanning calorimeter (DSC). The heat of fusion is calculated from the area of the endothermic peak of DSC and the mass of the thermoplastic resin component. When an inorganic filler or the like is contained in the solid binder, the heat of fusion is calculated from the mass of the resin component other than the inorganic filler.
[0137] Specifically, the so-called amorphous thermoplastic resin in the present disclosure refers to a resin having the characteristics measured by the following steps. 2 to 10 mg of a sample is weighed and placed in an aluminum pan, and the temperature is raised from 23°C to 200°C or above at 10°C / min by DSC (DSC8231 manufactured by Rigaku Co., Ltd.) to obtain a DSC curve. Then, the heat of fusion is calculated using the area of the endothermic peak during melting obtained from the DSC curve and the above-mentioned weighed value, and a substance with a heat of fusion of 15 J / g or less is regarded as an amorphous thermoplastic resin.
[0138] From the perspective of sufficiently imparting the properties of the amorphous thermoplastic resin to the solid adhesive, the content of the amorphous thermoplastic resin is preferably 60% by mass or more, more preferably 70% by mass or more, further preferably 80% by mass or more, and most preferably 90% by mass or more of the resin component in the solid adhesive.
[0139] The heat of fusion is 15 J / g or less, preferably 11 J / g or less, more preferably 7 J / g or less, and further preferably 4 J / g or less, and the endothermic peak during melting is most preferably below the detection limit.
[0140] The epoxy equivalent is 1,600 or more, preferably 2,000 or more, more preferably 5,000 or more, further preferably 9,000 or more, and most preferably it is at least the detection limit and substantially no epoxy group is detected.
[0141] By using the solid adhesive, when heated, the viscosity does not drop sharply as observed in conventional hot melt adhesives, and the viscosity does not reach a low state (0.001 to 100 Pa·s) even in a high temperature range exceeding 200° C. Therefore, the solid adhesive does not flow out of the laminate even in a molten state, and the thickness of the adhesive layer can be stably ensured, and a high adhesive force can be stably obtained.
[0142] The epoxy equivalent in the present disclosure (the mass of the above-mentioned resin containing 1 mol of epoxy groups) is the value of the epoxy equivalent of the thermoplastic epoxy resin or phenoxy resin component contained in the solid adhesive before bonding, and is a value measured by the method specified in JIS K 7236:2001 (unit: "g / eq."). Specifically, the epoxy equivalent of the resin is measured using a potentiometric titration apparatus, cyclohexanone as a solvent, tetraethylammonium bromide acetic acid solution is added to the resin, and a 0.1 mol / L perchloric acid-acetic acid solution is used. For solvent-diluted products (resin varnishes), it is calculated in the form of a numerical value as a solid content conversion value based on the non-volatile component. The epoxy equivalent of a mixture of two or more resins can also be calculated from the content and epoxy equivalent of each resin.
[0143] The melting point of the amorphous thermoplastic resin as the main component of the solid adhesive is preferably 50°C to 400°C, more preferably 60°C to 350°C, and even more preferably 70°C to 300°C. When the melting point is in the range of 50°C to 400°C, the solid adhesive is efficiently deformed and melted by heating, and wets and spreads effectively on the bonding surface, so that high bonding strength can be obtained. In the present disclosure, the melting point of the amorphous thermoplastic resin refers to the temperature at which the solid is substantially softened and becomes thermoplastic, and can be melted and bonded.
[0144] In the past, it was difficult to disassemble the joint body containing a thermosetting adhesive, and it was difficult to separate the heterogeneous materials constituting the joint body for recycling (i.e., poor recyclability). In addition, when a thermosetting adhesive is used, it is difficult to re-stick when there is a misalignment of the joining position during the manufacturing process of the joint body, or when the adherend has defects and needs to be replaced (i.e., poor repairability), which lacks convenience. On the other hand, the above-mentioned solid adhesive can be softened and melted by heat, and two adherends can be easily separated, so it has excellent recyclability. In addition, since the above-mentioned solid adhesive is thermoplastic, it can be reversibly softened, melted and cured (solidified) repeatedly, and it also has excellent repairability.
[0145] 《Thermoplastic Epoxy Resin》
[0146] The thermoplastic epoxy resin is preferably a polymer of (a) a bifunctional epoxy resin monomer or oligomer and (b) a bifunctional compound having two identical or different functional groups selected from phenolic hydroxyl, carboxyl, mercapto, isocyanate and cyanate groups. By using such a compound, the polymerization reaction to form a linear polymer proceeds preferentially, and a thermoplastic epoxy resin having desired properties can be formed.
[0147] The (a) bifunctional epoxy resin monomer or oligomer mentioned above refers to an epoxy resin monomer or oligomer having two epoxy groups in the molecule. Examples of the (a) bifunctional epoxy resin monomer or oligomer include bisphenol A type epoxy resin, bisphenol F type epoxy resin, bifunctional phenol novolac type epoxy resin, bisphenol AD type epoxy resin, biphenyl type epoxy resin, bifunctional naphthalene type epoxy resin, bifunctional alicyclic epoxy resin, bifunctional glycidyl ester type epoxy resin (e.g., diglycidyl phthalate, diglycidyl tetrahydrophthalate, diglycidyl dimer acid diglycidyl ester, etc.), bifunctional glycidyl amine type epoxy resin (e.g., diglycidyl aniline, diglycidyl toluidine, etc.), bifunctional heterocyclic epoxy resin, bifunctional diaryl sulfone type epoxy resin, hydroquinone type epoxy resin (e.g., hydroquinone diglycidyl ether, 2,5-dihydroquinone diglycidyl ether, etc.), and difunctional diphenylamine type epoxy resin. -tert-butylhydroquinone diglycidyl ether, resorcinol diglycidyl ether, etc.), bifunctional alkylene glycidyl ether compounds (for example, butanediol diglycidyl ether, butenediol diglycidyl ether, butynediol diglycidyl ether, etc.), bifunctional glycidyl group-containing hydantoin compounds (for example, 1,3-diglycidyl-5,5-dialkylhydantoin, 1-glycidyl-3-(glycidyloxyalkyl)-5,5-dialkylhydantoin, etc.), bifunctional glycidyl group-containing siloxanes (for example, 1,3-bis(3-glycidyloxypropyl)-1,1,3,3-tetramethyldisiloxane, α,β-bis(3-glycidyloxypropyl)polydimethylsiloxane, etc.), and modified products thereof. Among them, bisphenol A type epoxy resin, bisphenol F type epoxy resin, bisphenol S type epoxy resin, and biphenyl type epoxy resin are preferable in view of reactivity and handling properties.
[0148] Examples of the bifunctional compound having a phenolic hydroxyl group of (b) include mononuclear aromatic dihydroxy compounds having one benzene ring such as catechol, resorcinol, and hydroquinone, bisphenol compounds such as bis(4-hydroxyphenyl)propane (bisphenol A), bis(4-hydroxyphenyl)methane (bisphenol F), and bis(4-hydroxyphenyl)ethane (bisphenol AD), compounds having a condensed ring such as dihydroxynaphthalene, bifunctional phenol compounds into which an allyl group is introduced such as diallylresorcinol, diallylbisphenol A, and triallyldihydroxybiphenyl, and dibutylbisphenol A.
[0149] Examples of the bifunctional compound having a carboxyl group (b) include adipic acid, succinic acid, malonic acid, cyclohexanedicarboxylic acid, phthalic acid, isophthalic acid, and terephthalic acid.
[0150] Examples of the bifunctional compound having a mercapto group (b) include ethylene glycol bismercaptoacetate and ethylene glycol bismercaptopropionate.
[0151] Examples of the bifunctional compound having an isocyanate group (b) include diphenylmethane diisocyanate (MDI), isophorone diisocyanate (IPDI), hexamethylene diisocyanate (HMDI), and toluene diisocyanate (TDI).
[0152] Examples of the bifunctional compound having a cyanate group (b) include 2,2-bis(4-cyanatephenyl)propane, 1,1-bis(4-cyanatephenyl)ethane, and bis(4-cyanatephenyl)methane.
[0153] In the above (b), the bifunctional compound having a phenolic hydroxyl group is preferred because it can form a thermoplastic polymer having suitable properties. The bifunctional compound having two phenolic hydroxyl groups and a bisphenol structure or a biphenyl structure is preferred from the viewpoint of heat resistance and adhesion. Bisphenol A, bisphenol F and bisphenol S are preferred from the viewpoint of heat resistance and cost.
[0154] When (a) is a bisphenol A epoxy resin, a bisphenol F epoxy resin, a bisphenol S epoxy resin, or a biphenyl epoxy resin, and (b) is bisphenol A, bisphenol F, or bisphenol S, the polymer obtained by polymerization of (a) and (b) has: a main chain having a p-phenylene structure and an ether bond as the main skeleton, which are connected by an alkylene group; and a structure in which a hydroxyl group generated by addition polymerization is arranged in a side chain. The mechanical strength of the polymer after polymerization can be improved by the linear structure resulting from the main skeleton having a p-phenylene structure and an ether bond, and the adhesion to the substrate can be improved by the hydroxyl group arranged in the side chain. As a result, a high bonding strength at the same level as that of a thermosetting resin can be achieved while maintaining operability. Furthermore, by softening and melting by heat, it is possible to recycle and repair, which is a problem in thermosetting resins, and can improve recyclability and repairability.
[0155] 《Phenoxy resin》
[0156] Phenoxy resin is a polyhydroxy polyether synthesized from bisphenol compounds and epichlorohydrin, and has thermoplasticity. As a method for manufacturing phenoxy resin, it is known that a method using a direct reaction of a diphenol compound with epichlorohydrin and a method using a polyaddition reaction of a diglycidyl ether of a diphenol compound with a diphenol compound are used, and phenoxy resin can be a substance obtained by any method. In the case of a direct reaction of a diphenol compound with epichlorohydrin, as a diphenol compound, for example, phenol compounds such as bisphenol A, bisphenol F, bisphenol S, biphenol, biphenylene glycol, and diphenylfluorene can be cited. Among them, from the viewpoint of cost, adhesion, viscosity, and heat resistance, bisphenol A, bisphenol F, and bisphenol S are preferably used. In addition to diphenol compounds, aliphatic diols such as ethylene glycol, propylene glycol, and diethylene glycol can be included in the above-mentioned direct reaction. They can be used alone or in combination of two or more. The phenoxy resin has a chemical structure similar to that of the epoxy resin, and has a main chain having a p-phenylene structure and an ether bond as a main skeleton and connecting them, and a structure in which hydroxyl groups are arranged in side chains.
[0157] 《Thermoplastic epoxy resins and phenoxy resins》
[0158] The weight average molecular weight of the thermoplastic epoxy resin and the phenoxy resin is preferably 10,000 to 500,000, more preferably 18,000 to 300,000, and further preferably 20,000 to 200,000, as measured by polystyrene conversion of GPC (gel permeation chromatography). The weight average molecular weight is a standard polystyrene conversion value calculated by the dissolution peak position detected by GPC. If the weight average molecular weight is within the above range, the balance between thermoplasticity and heat resistance is good, so the joint body can be formed efficiently by melting, and the heat resistance of the joint body can also be improved. If the weight average molecular weight is 10,000 or more, the heat resistance is excellent, and if it is 500,000 or less, the viscosity during melting is low, and the adhesion becomes high.
[0159] 《Method for producing solid adhesive》
[0160] The method for producing the solid binder is not particularly limited, and for example, the solid binder can be obtained by heating a monomer or oligomer of a bifunctional epoxy compound to polymerize it. In order to reduce the viscosity during polymerization and facilitate stirring, a solvent can be added. When a solvent is added, it needs to be removed, and the solid binder can be obtained by drying or polymerizing or both on a release film or the like.
[0161] As required, other additives may be mixed into the solid binder within a range that does not hinder the effect of the present invention. The amount of the additive mixed relative to the total amount of the amorphous thermoplastic resin is preferably 50% by volume or less, more preferably 30% by volume or less, further preferably 20% by volume or less, and most preferably 10% by volume or less. The volume % of the additive in the present disclosure means the volume ratio of the additive contained in the monomer or oligomer of the bifunctional epoxy compound before polymerization based on the volume of the total amount of the amorphous thermoplastic resin. The volume of the additive can be obtained by dividing the mass of the additive contained by the true specific gravity of the additive.
[0162] As the above-mentioned additives, for example, viscosity modifiers, inorganic fillers, organic fillers (resin powders), defoamers, coupling agents such as silane coupling agents, and pigments can be mentioned. These additives can be used alone or in combination of two or more. As viscosity modifiers, for example, reactive diluents can be mentioned. As inorganic fillers, for example, spherical fused silica, metal powders of metals such as iron, silica sand, talc, calcium carbonate, mica, acid clay, diatomaceous earth, kaolin, quartz, titanium oxide, silicon dioxide, phenolic resin microspheres, and glass balls can be mentioned.
[0163] The solid adhesive thus obtained has a low content of unreacted monomers or terminal epoxy groups, or contains substantially no unreacted monomers or terminal epoxy groups, and therefore has excellent storage stability and can be stored for a long period of time at room temperature.
[0164] The form of the solid adhesive before melting is not particularly limited, and preferably has any shape selected from a film, a rod, a particle, and a powder. At least one side of the outer shape of the solid adhesive is preferably 5 mm or less, more preferably 3 mm or less, further preferably 1 mm or less, particularly preferably 0.5 mm or less, and most preferably 0.3 mm or less. By sandwiching a solid adhesive having at least one side of an outer shape of 5 mm or less between the first member and the second member, heating and pressurizing, the solid adhesive is efficiently expanded on the bonding surface, so that a high bonding force can be obtained.
[0165] The solid adhesive before melting is more preferably in a film shape. The solid adhesive in a film shape can join these metal components while reliably maintaining the components to be joined with each other at a prescribed interval throughout the entire joining surface. Therefore, the solid adhesive in a film shape is particularly advantageous from the perspective of dimensional stability of the laminate. The thickness of the solid adhesive in a film shape is preferably 10 μm to 5 mm, more preferably 20 μm to 3 mm, and further preferably 30 μm to 0.5 mm. By making the thickness of the solid adhesive in a film shape greater than 10 μm, electrolytic corrosion between the first component and the second component can be more reliably prevented, and the bonding strength can be ensured. By making the thickness of the solid adhesive in a film shape less than 5 mm, the bonding strength in the shear direction of the joining surface can be increased.
[0166] The solid adhesive may have viscosity within a range that does not impair the adhesive force and heat resistance. In this case, the solid adhesive may be temporarily fixed to the substrate in the laminate preparation step.
[0167] From the viewpoint of adhesiveness, the average thickness of the adhesive layer is preferably 1 μm to 5000 μm, more preferably 20 μm to 1000 μm, and further preferably 50 μm to 800 μm.
[0168] (Heat sink)
[0169] The laminated body of the present disclosure may include a heat sink on the first resin layer side surface of the first conductive layer or the second resin layer side surface of the second conductive layer.
[0170] As the heat sink, a conventionally known one can be used, and components and the like can be bonded thereto.
[0171] (use)
[0172] The laminated body disclosed in the present invention can be suitably used in the manufacture of a power module (PM).
[0173] The application of the laminated body disclosed in the present invention is not limited to PM applications, and can be used in other electrical components, control components, drive components, weak current connections, home appliances, cosmetic components, etc.
[0174] Below, refer to Figure 1 to Figure 6 An embodiment of the laminated body and the like disclosed in the present invention will be described. Figure 1 to Figure 6 The form shown.
[0175] Figure 1 This is a perspective view showing one embodiment of the laminated body disclosed herein. Figure 2 It is a perspective view showing another embodiment of the laminated body disclosed in the present invention.
[0176] about Figure 1 and Figure 2, the display of the bonding layer between layers is omitted.
[0177] Figure 1 The laminated body 10 shown includes a first resin layer 11, a first conductive layer 12, an insulating layer 13, a second conductive layer 14, and a second resin layer 16 in this order.
[0178] Figure 2 The laminated body 20 shown includes a first resin layer 21, a first conductive layer 22, an insulating layer 23, a second conductive layer 24, and a second resin layer 26 in this order.
[0179] like Figure 1 and Figure 2 As shown, the second resin layer may have an opening. Thus, a heat sink or the like can be disposed on the surface of the second conductive layer or the like. The shape of the opening is not particularly limited, and is preferably appropriately adjusted according to the intended use.
[0180] like Figure 1 and Figure 2 As shown in the figure, the first conductive layer and the second conductive layer may protrude outward from the outer periphery of the first resin layer and the second resin layer, thereby enabling connection with other members such as wiring.
[0181] Figure 3 This is a cross-sectional view showing one embodiment of the laminated body disclosed herein.
[0182] Figure 3 The laminated body 30 shown includes a first resin layer 31 , an adhesive layer 35 , a first conductive layer 32 , an adhesive layer 35 , an insulating layer 33 , an adhesive layer 35 , a second conductive layer 34 , an adhesive layer 35 , and a second resin layer 36 .
[0183] like Figure 3 As shown, the first resin layer 31 has a housing portion including a stepped recessed portion, and the adhesive layer 35 , the first conductive layer 32 , the adhesive layer 35 , the insulating layer 33 , the adhesive layer 35 , the second conductive layer 34 and the adhesive layer 35 are arranged in the housing portion.
[0184] exist Figure 3 In the embodiment, the first conductive layer, the insulating layer, and the second conductive layer are accommodated in different layers of the stepped concave portion. Thus, thermal durability can be improved.
[0185] exist Figure 3 In the illustrated laminate 30 , the first resin layer 31 and the second resin layer 36 are bonded together via an adhesive layer 35 .
[0186] Figure 4 It is a cross-sectional view showing another embodiment of the laminated body disclosed in the present invention.
[0187] Figure 4The laminated body 40 shown includes a first resin layer 41 , an adhesive layer 45 , a first conductive layer 42 , an adhesive layer 45 , an insulating layer 43 , an adhesive layer 45 , a second conductive layer 44 , an adhesive layer 45 , and a second resin layer 46 .
[0188] like Figure 4 As shown, the first resin layer 41 has a housing portion including a stepped recessed portion, and the adhesive layer 45, the first conductive layer 42, the adhesive layer 45, the insulating layer 43, the adhesive layer 45, the second conductive layer 44 and the adhesive layer 45 are arranged in the housing portion.
[0189] exist Figure 4 In the embodiment, the first conductive layer, the insulating layer, and the second conductive layer are accommodated in different layers of the stepped concave portion. Thus, thermal durability can be improved.
[0190] In addition, if Figure 4 As shown, the first resin layer 41 has an insertion portion 47 inserted into an opening (not shown) of the second resin layer 46 .
[0191] In addition, Figure 4 In the illustrated laminate 40 , a first resin layer 41 and a second resin layer 46 are bonded together via an adhesive layer 45 .
[0192] Figure 5 It is a cross-sectional view showing another embodiment of the laminated body disclosed in the present invention.
[0193] Figure 5 The laminated body 50 shown includes a first resin layer 51 , a heat sink 57 , an adhesive layer 55 , a first conductive layer 52 , an adhesive layer 55 , an insulating layer 53 , an adhesive layer 55 , a second conductive layer 54 , an adhesive layer 55 , and a second resin layer 56 .
[0194] like Figure 5 As shown, the first resin layer 51 has a receiving portion including a stepped recessed portion, and a heat sink 57, an adhesive layer 55, a first conductive layer 52, an adhesive layer 55, an insulating layer 53, an adhesive layer 55, a second conductive layer 54 and an adhesive layer 55 are arranged in the receiving portion.
[0195] exist Figure 5 In the embodiment, the first conductive layer, the insulating layer, and the second conductive layer are accommodated in different layers of the stepped concave portion. Thus, thermal durability can be improved.
[0196] In addition, Figure 5 In the illustrated laminate 50 , a first resin layer 51 and a second resin layer 56 are bonded together via an adhesive layer 55 .
[0197] Figure 6 This is a perspective view showing one embodiment of the first resin layer included in the laminate of the present disclosure.
[0198] like Figure 6 As shown, the first resin layer 100 has a plurality of housing portions 101 including concave portions 102A and convex portions 102B.
[0199] Furthermore, the first resin layer 100 includes a fixing portion 103 and an opening 104 .
[0200] like Figure 6 As shown, the first resin layer 100 may have openings between the housing portions 101. Thus, another member such as wiring can be connected to the first resin layer and the like disposed on the first resin layer 100.
[0201] like Figure 3 to Figure 6 As shown in the figure, the sizes of the peripheries of the adhesive layer, the first conductive layer, the insulating layer, and the second conductive layer may be different. When the sizes of the peripheries of the adhesive layer, the first conductive layer, the insulating layer, and the second conductive layer are different, the size of the inner periphery of the concave portion of the first resin layer is preferably greater than the size of the periphery of the layer having the largest periphery among the adhesive layer, the first conductive layer, the insulating layer, and the second conductive layer.
[0202] [Method for producing laminate]
[0203] The method for producing a laminate disclosed herein comprises the following steps:
[0204] a step of preparing a first resin layer having a receiving portion on at least one surface; and
[0205] a lamination step of laminating a first conductive layer, an insulating layer and a second conductive layer on the surface of the first resin layer;
[0206] In the lamination step, at least the first conductive layer is disposed in the housing portion of the first resin layer.
[0207] According to the method for producing a laminated body disclosed in the present invention, a laminated body having excellent thermal durability can be produced. The reason why the above-mentioned effect is exerted is not clear, but it is presumed as follows.
[0208] The manufacturing method of the laminated body disclosed in the present invention is not manufactured by insert molding, but by separately manufacturing each layer and laminating. Therefore, for the laminated body manufactured by insert molding, the first conductive layer is buried in the first resin layer and is completely in close contact. On the contrary, for the laminated body manufactured by the manufacturing method disclosed in the present invention, the first resin layer and the first conductive layer are not completely in close contact, which can alleviate the internal stress generated during heating. It is inferred that the generation of cracks and the deformation of the conductive layer and the resin layer can be suppressed, and the thermal durability is improved.
[0209] The method for producing a laminated body disclosed herein may include a second laminating step of further laminating a second resin layer on the side of the second conductive layer opposite to the insulating layer.
[0210] (Preparation process)
[0211] Since the first resin layer has been described above, its description is omitted here.
[0212] The method for producing the first resin layer is not particularly limited, and the first resin layer can be produced by insert molding or the like.
[0213] (Lamination process)
[0214] The method for producing a laminated body disclosed in the present invention includes a lamination step of laminating a first conductive layer, an insulating layer, and a second conductive layer on a surface of a first resin layer.
[0215] In the lamination step, at least the first conductive layer is disposed in the housing portion of the first resin layer. Preferably, the first insulating layer and the second conductive layer are disposed in the housing portion of the resin layer.
[0216] The lamination of the first conductive layer, the insulating layer, and the second conductive layer on the surface of the first resin layer can be performed by placing an adhesive layer between the layers and heating.
[0217] When an adhesive layer is disposed between the layers, it is preferable that the adhesive layer is disposed in the housing portion of the first resin layer together with the first conductive layer, the insulating layer, and the second conductive layer in the lamination step.
[0218] In the lamination step, a heat sink may be disposed on the side of the first conductive layer opposite to the insulating layer or on the side of the second conductive layer opposite to the insulating layer.
[0219] When a heat sink is disposed, it is preferable that the heat sink is disposed in the housing portion of the first resin layer together with the first conductive layer, the insulating layer, and the second conductive layer in the lamination step.
[0220] Since the first conductive layer, the second conductive layer, the insulating layer, the adhesive layer, and the heat sink have been described above, their description is omitted here.
[0221] The first conductive layer, the second conductive layer, the insulating layer, the adhesive layer, and the heat sink may be those produced by a conventionally known method, or may be commercially available products.
[0222] (Second Lamination Process)
[0223] Since the second resin layer has been described above, its description is omitted here.
[0224] The method for producing the second resin layer is not particularly limited, and the second resin layer can be produced by insert molding or the like.
[0225] The lamination of the second resin layer can be performed by placing an adhesive layer between the second resin layer and the second conductive layer and heating the layer.
[0226] Furthermore, the first resin layer and the second resin layer may be bonded together via an adhesive layer.
[0227] When the first resin layer has either one of the insertion portion and the opening portion and the second resin layer has at least the other, the first resin layer and the second resin layer can be fitted together by inserting the insertion portion into the opening portion.
[0228] The lamination step using the solid adhesive and the second lamination step will be described in more detail.
[0229] 〈Pre-joining process〉
[0230] In the pre-bonding step, a laminated body is formed in which a first member, a solid bonding agent having an amorphous thermoplastic resin as a main component, and a second member are sequentially arranged, wherein the amorphous thermoplastic resin is at least one selected from a thermoplastic epoxy resin and a phenoxy resin. In the laminated body, the first member and the solid bonding agent, and the solid bonding agent and the second member are not bonded to each other, and the independent members are overlapped.
[0231] 〈Joining process〉
[0232] In the bonding step, the stacked body is heated and pressurized to melt the solid bonding agent, and then the temperature is lowered to solidify the solid bonding agent, thereby bonding the first member and the second member.
[0233] The temperature during the heating and pressurizing is preferably 100° C. to 400° C., more preferably 120° C. to 350° C., and even more preferably 150° C. to 300° C. By heating at 100° C. to 400° C., the solid adhesive is efficiently deformed and melted to effectively wet and spread on the bonding surface, thereby obtaining high adhesive strength.
[0234] The pressure in the above-mentioned heating and pressurizing is preferably 0.01MPa to 20MPa, more preferably 0.1MPa to 10MPa, and further preferably 0.2MPa to 5MPa. The pressure here refers to the average pressure in the bonding surface of the first component and the second component. By applying pressure at 0.01MPa to 20MPa, the above-mentioned solid adhesive is efficiently deformed and effectively wets and spreads on the bonding surface, so that a high bonding force can be obtained. In the case where at least one of the first component or the second component contains a thermoplastic resin on the bonding surface, by applying pressure at 0.01MPa to 20MPa, the solid adhesive can be compatible with the thermoplastic resin of the component, thereby obtaining a high bonding force.
[0235] Thermoplastic epoxy resins and phenoxy resins, which are main components of solid adhesives, have low cohesive strength within the resin and have hydroxyl groups, so they interact strongly with the substrate and can bond dissimilar materials with higher adhesive strength than conventional crystalline hot melt adhesives.
[0236] The bonding of the first member and the second member utilizes the phase change (solid-liquid-solid) of the solid adhesive, and since it is not accompanied by a chemical reaction, the bonding can be completed in a shorter time than with conventional thermosetting epoxy resins.
[0237] Sometimes, high bonding strength is obtained by performing appropriate pre-treatment on the first component or the second component or both. As pre-treatment, it is preferred that the surface of the substrate is washed or a pre-treatment is formed on the surface. The pre-treatment can be only one, or two or more can be implemented. As the specific method of these pre-treatments, known methods can be used.
[0238] Specifically, when the material of the above-mentioned component is metal, it is preferably at least one selected from the group consisting of degreasing treatment, UV ozone treatment, blasting treatment, grinding treatment, plasma treatment, and etching treatment. When the material of the above-mentioned component is resin, it is preferably at least one selected from the group consisting of degreasing treatment, UV ozone treatment, blasting treatment, grinding treatment, plasma treatment, and corona discharge treatment.
[0239] exist Fig. 9 In the shown joint body 1, the first component 3 and the second component 4 are joined and integrated via the adhesive layer 2 solidified after the above-mentioned solid adhesive is melted, and the joint body 1 of the first component 3 and the second component 4 shows excellent joint strength. The joint strength is affected by a large number of factors such as the thickness of the adhesive layer, the molecular weight and chemical structure of the polymer constituting the adhesive, mechanical properties, and viscoelastic properties, in addition to the strength of the interface interaction that works between the adhesive layer and the substrate. Therefore, the details of the mechanism by which the joint body of the present disclosure shows excellent joint strength are unclear, but it is speculated that the cohesive force of the amorphous thermoplastic resin constituting the adhesive layer is low, and there is a hydroxyl group in the resin, and the chemical bonds or intermolecular forces such as hydrogen bonds, van der Waals forces are formed at the interface between the adhesive layer and the first component and the interface between the adhesive layer and the second component as the main factors. However, in a bonded body, the state or characteristics of the interface of the bonded body are difficult to analyze due to the extremely thin chemical structure with a thickness below the nanometer level. It is impossible or impractical with current technology to identify the state or characteristics of the interface of the bonded body disclosed herein so as to distinguish it from a bonded body that does not contain the solid bonding agent disclosed herein.
[0240] The laminate of the present disclosure whose adhesive layer comprises an amorphous thermoplastic resin has excellent recyclability and repairability, and can be easily separated into the first member and the second member, that is, the first (second) conductive layer and the insulating layer by heating the bonded body, thereby disassembling the laminate.
[0241] Example
[0242] The following shows implementation test examples and comparative test examples related to the present invention, but the present invention is not limited thereto. In the following examples, the first member and the second member are collectively referred to as a bonding substrate.
[0243] 〈Bonding base material〉
[0244] The following bonding substrates were used.
[0245] 《PPS (resin)》
[0246] An injection molded body (45 mm in length×10 mm in width×3 mm in thickness) obtained by injection molding polyphenylene sulfide (FZ-1130-D5 manufactured by DIC Corporation) (resin temperature: 300° C., mold temperature: 140° C.) was used without surface treatment.
[0247] "copper"
[0248] The surface of copper (C1100 (Tough Pitch Copper)) was wiped with methyl ethyl ketone for degreasing treatment, and a test piece having a width of 18 mm, a length of 45 mm, and a thickness of 3 mm was obtained.
[0249] 〈Weight average molecular weight, heat of fusion and epoxy equivalent of thermoplastic epoxy resin and phenoxy resin〉
[0250] The weight average molecular weight, heat of fusion and epoxy equivalent of the thermoplastic epoxy resin and phenoxy resin were determined by the following steps, respectively.
[0251] (Weight average molecular weight)
[0252] The thermoplastic epoxy resin and the phenoxy resin were dissolved in tetrahydrofuran, and measured under the following conditions using Prominence 501 (manufactured by Showa Science Corporation, detector: Shodex (registered trademark) RI-501 (manufactured by Showa Denko K.K.)).
[0253] Column: LF-804 manufactured by Showa Denko K.K. × 2
[0254] Column temperature: 40°C
[0255] Sample: 0.4 mass% tetrahydrofuran solution of resin
[0256] Flow rate: 1mL / min
[0257] Eluent: Tetrahydrofuran
[0258] Calibration method: conversion using standard polystyrene
[0259] (Heat of Fusion)
[0260] 2 to 10 mg of a thermoplastic epoxy resin and a phenoxy resin were weighed and placed in an aluminum pan, and the temperature was raised from 23°C to 200°C at 10°C / min using a DSC (DSC8231 manufactured by Rigaku Corporation) to obtain a DSC curve. The heat of fusion was calculated from the area of the endothermic peak during melting of the obtained DSC curve and the weighed value.
[0261] (Epoxy Equivalent Weight)
[0262] The measured value obtained in accordance with JIS K 7236: 2001 was converted into a value as a resin solid content. In the case of a simple mixture without reaction, it was calculated from the respective epoxy equivalents and contents.
[0263] <Implementation Test Example 1>
[0264] (Solid adhesive P-1)
[0265] In a reaction apparatus equipped with a stirrer, a reflux cooler, a gas introduction pipe, and a thermometer, 203 g (1.0 equivalent) of jER (registered trademark) 1007 (manufactured by Mitsubishi Chemical Co., Ltd., bisphenol A type epoxy resin, weight average molecular weight of about 10,000), 12.5 g (1.0 equivalent) of bisphenol S, 2.4 g of triphenylphosphine, and 1,000 g of methyl ethyl ketone were added, and the mixture was heated to 100° C. while stirring under a nitrogen atmosphere. Dissolution was confirmed by visual observation, and the mixture was cooled to 40° C. to obtain a resin composition having a solid content of about 20% by mass. The solvent was removed from the resin composition to obtain a solid. A non-adhesive fluororesin film (Nitorfluon (registered trademark) No. 900UL, manufactured by Nitto Denko Corporation) was set on the upper and lower plates of the press, and the above solid was arranged on the non-adhesive fluororesin film of the lower plate, and then the press was heated to 160°C, and the above resin composition was heated and compressed for 2 hours to obtain a film-like solid adhesive (P-1) with a solid content of 100% by mass and a thickness of 100 μm. The weight average molecular weight was about 37,000. The epoxy equivalent was above the detection limit. No melting heat peak was detected in DSC.
[0266] (Joint body)
[0267] As a bonded body, the following one (resin / metal) was produced.
[0268] 《Resin / Metal》
[0269] The solid adhesive P-1 cut into a size of 10×15 mm was placed on the copper substrate (first member), and then the PPS substrate (second member) was quickly placed thereon. The overlap between these substrates was set to a width of 10 mm and a depth of 5 mm. The solid adhesive P-1 was placed in a manner that completely covered the overlapping area between the substrates. That is, the first member and the second member were not in direct contact with each other, and an unbonded laminate was prepared as a state in which the solid adhesive was present between them.
[0270] A high-frequency induction welding machine (manufactured by Seidensha Electronics Co., Ltd., vibrator UH-2.5K, press JIIP30S) was used to heat the metal by high-frequency induction, and the test pieces were joined together by heating and pressurizing. The pressure was set to 110N (pressure 2.2MPa), the vibration frequency was set to 900kHz, and the vibration time was set to 6 seconds.
[0271] The following steps were performed to produce a joint for open time evaluation. The solid adhesive P-1 cut into a size of 10×15 mm was placed on the copper substrate (first component), and then the PPS substrate (second component) was placed thereon after being left to stand for 3 days. The overlap between these substrates was set to a width of 10 mm and a depth of 5 mm. The solid adhesive P-1 was placed in a manner that completely covered the overlapping area between the substrates. That is, the first component and the second component were not in direct contact with each other, and an unjoined laminate was prepared as a state in which the solid adhesive existed between them.
[0272] A high-frequency induction welding machine (manufactured by Seidensha Electronics Co., Ltd., vibrator UH-2.5K, press JIIP30S) was used to heat the metal by high-frequency induction, and the test pieces were joined together by heating and pressurizing. The pressure was set to 110N (pressure 2.2MPa), the vibration frequency was set to 900kHz, and the vibration time was set to 5 seconds.
[0273] <Implementation Test Example 2>
[0274] (Solid adhesive P-2)
[0275] In a reaction apparatus equipped with a stirrer, a reflux cooler, a gas introduction pipe, and a thermometer, 20 g of フェノトート (registered trademark) YP-50S (manufactured by Nippon Tetsu Chemical & Material Co., Ltd., a phenoxy resin with a weight average molecular weight of about 50,000) and 80 g of cyclohexanone were added, and the temperature was raised to 60° C. while stirring, and the dissolution was confirmed by visual observation, and the resin composition with a solid content of 20% by mass was obtained by cooling to 40° C. The solvent was removed from the resin composition to obtain a solid. A non-adhesive fluororesin film (Nitorfluon (registered trademark) No. 900UL, manufactured by Nitto Denko Corporation) was set on the upper and lower plates of the press, and the above solid was arranged on the non-adhesive fluororesin film of the lower plate, and then the press was heated to 160°C, and the above resin composition was heated and compressed for 2 hours to obtain a film-like solid adhesive (P-2) with a solid content of 100% by mass and a thickness of 100 μm. The weight average molecular weight was 50,000, and the epoxy equivalent was above the detection limit. No melting heat peak was detected in DSC.
[0276] (Joint body)
[0277] The joined bodies and joined bodies for open time evaluation shown in Table 1 were produced in the same manner as in Test Example 1 except that P-2 was used as the solid joining agent.
[0278] <Implementation Test Example 3>
[0279] (Solid adhesive P-3)
[0280] The resin composition P-2 and crystalline epoxy resin YSLV-80XY (manufactured by Nippon Steel Chemical & Material Co., Ltd.) were mixed at a mass ratio of 98:2 to obtain a solid adhesive (P-3) having a weight average molecular weight of 36,000, an epoxy equivalent of 9600 g / eq, and a heat of fusion of 2 J / g.
[0281] (Joint body)
[0282] The joined bodies and joined bodies for open time evaluation shown in Table 1 were produced in the same manner as in Test Example 1 except that P-3 was used as the solid joining agent.
[0283] <Implementation Test Example 4>
[0284] (Solid cement P-4)
[0285] The resin composition P-2 and crystalline epoxy resin YSLV-80XY (manufactured by Nippon Steel Chemical & Material Co., Ltd.) were mixed at a mass ratio of 94:6 to obtain a solid adhesive (P-4) having a weight average molecular weight of 35,000, an epoxy equivalent of 2100 g / eq, and a heat of fusion of 4 J / g.
[0286] (Joint body)
[0287] The joined bodies and joined bodies for open time evaluation shown in Table 1 were produced in the same manner as in Test Example 1 except that P-4 was used as the solid joining agent.
[0288] <Implementation Test Example 5>
[0289] (Solid cement P-5)
[0290] The resin composition P-2 and crystalline epoxy resin YSLV-80XY (manufactured by Nippon Steel Chemical & Material Co., Ltd.) were mixed at a mass ratio of 89:11 to obtain a solid adhesive (P-5) having a weight average molecular weight of 33,000, an epoxy equivalent of 1745 g / eq, and a heat of fusion of 11 J / g.
[0291] (Joint body)
[0292] The joined bodies and joined bodies for open time evaluation shown in Table 1 were produced in the same manner as in Test Example 1 except that P-5 was used as the solid joining agent.
[0293] <Implementation Test Example 6>
[0294] (Solid cement P-6)
[0295] In a reaction apparatus equipped with a stirrer, a reflux cooler, a gas introduction pipe, and a thermometer, 203 g (1.0 equivalent) of jER (registered trademark) 1007 (manufactured by Mitsubishi Chemical Co., Ltd., bisphenol A type epoxy resin, molecular weight about 4060), 12.5 g (0.6 equivalent) of bisphenol S (molecular weight 250), 2.4 g of triphenylphosphine, and 1,000 g of methyl ethyl ketone were added, and the temperature was raised to 100° C. while stirring under a nitrogen atmosphere. Dissolution was confirmed by visual observation, and the mixture was cooled to 40° C. to obtain a resin composition having a solid content of about 20% by mass. The solvent was removed from the resin composition to obtain a solid. A non-adhesive fluororesin film (Nitorfluon (registered trademark) No. 900UL, manufactured by Nitto Denko Corporation) was set on the upper and lower plates of the press, and the above solid was arranged on the non-adhesive fluororesin film of the lower plate, and then the press was heated to 160°C, and the above resin composition was heated and compressed for 2 hours to obtain a film-like solid adhesive (P-6) with a solid content of 100% by mass and a thickness of 100 μm. The weight average molecular weight was about 30,000, and the epoxy equivalent was above the detection limit. No melting heat peak was detected in DSC.
[0296] (Joint body)
[0297] The joined bodies and joined bodies for open time evaluation shown in Table 1 were produced in the same manner as in Test Example 1 except that P-6 was used as the solid joining agent.
[0298] <Comparative Test Example 1>
[0299] (Solid adhesive Q-1)
[0300] Two liquids of thermosetting liquid epoxy adhesive E-250 (manufactured by Conisy Co., Ltd., a two-component type of bisphenol epoxy resin and amine curing agent) were mixed, applied to a release film, cured at 100°C for 1 hour, cooled, and peeled off from the release film to obtain a film-like solid adhesive (Q-1) with a thickness of 100 μm. No melting heat peak was detected in DSC. The epoxy equivalent and weight average molecular weight could not be measured because it was insoluble in the solvent.
[0301] (Joint body)
[0302] The joined bodies and joined bodies for open time evaluation shown in Table 1 were produced in the same manner as in Test Example 1 except that Q-1 was used as the solid joining agent.
[0303] <Comparative Test Example 2>
[0304] (Solid adhesive Q-2)
[0305] As the solid bonded body Q-2, an amorphous polycarbonate film (Uriplon (registered trademark) FE2000, manufactured by Mitsubishi Engineering Plastics Co., Ltd., thickness 100 μm) was used. No melting heat peak was detected in DSC.
[0306] (Joint body)
[0307] The joined bodies and joined bodies for open time evaluation shown in Table 1 were produced in the same manner as in Test Example 1 except that Q-2 was used as the solid joining agent.
[0308] <Comparative Test Example 3>
[0309] (Solid adhesive Q-3)
[0310] Crystalline epoxy resin YSLV-80XY (manufactured by Nippon Steel Chemical & Material Co., Ltd.) was used as the solid binder (Q-3). The epoxy equivalent was 192 g / eq. The weight average molecular weight was 340. The heat of fusion was 70 J / g.
[0311] (Joint body)
[0312] The joined bodies and joined bodies for open time evaluation shown in Table 1 were produced in the same manner as in Test Example 1 except that Q-3 was used as the solid joining agent.
[0313] <Comparative Test Example 4>
[0314] (Joint body)
[0315] Two liquids of thermosetting liquid epoxy adhesive E-250 (manufactured by Conisy Co., Ltd., a two-component type of bisphenol epoxy resin and amine curing agent) were mixed, applied to the first member and the second member similar to the above-mentioned implementation test example 1, respectively, and bonded within 1 minute, then left to stand in an oven at 100°C for 1 hour in a state fixed by a jig to cure the adhesive component, and then cooled to room temperature to produce a bonded body shown in Table 1. A bonded body for open time evaluation was also produced in the same manner as above, except that the thermosetting liquid epoxy adhesive E-250 was applied to the first member and the second member, and then bonded after standing for 3 days.
[0316] <Comparative Test Example 5>
[0317] 203 g (1.0 equivalent) of jER (registered trademark) 1007 (manufactured by Mitsubishi Chemical Co., Ltd., bisphenol A type epoxy resin, weight average molecular weight of about 10,000), 12.5 g (1.0 equivalent) of bisphenol S, 2.4 g of triphenylphosphine, and 1,000 g of methyl ethyl ketone were added to a flask and stirred at room temperature to obtain a liquid resin composition having a solid content of about 20% by mass. The liquid resin composition was applied by rod coating on the second component similar to the above-mentioned Implementation Example 1, dried at room temperature for 30 minutes, and then allowed to stand in an oven at 160°C for 2 hours, thereby forming a solid thermoplastic epoxy resin polymer coating layer with a thickness of 100 μm on the surface of the second component. The weight average molecular weight of the coating layer is about 40,000. The epoxy equivalent is above the detection limit. No melting heat peak was detected in DSC.
[0318] (Joint body)
[0319] The same procedures as in Test Example 1 were followed except that the first member was directly disposed on the second member having the coating layer, thereby producing the joined bodies shown in Table 1. In order to evaluate the open time, the same procedures were followed except that the thermoplastic epoxy resin polymer coating layer was formed on the surface of the second member, left to stand for 3 days, and then laminated with the first member, thereby producing joined bodies for open time evaluation.
[0320] <Comparative Test Example 6>
[0321] In a reaction apparatus equipped with a stirrer, a reflux cooler, a gas inlet pipe, and a thermometer, 20 g of フェノトート (registered trademark) YP-50S (manufactured by Nippon Tetsu Chemical & Material Co., Ltd., a phenoxy resin with a weight average molecular weight of about 50,000) and 80 g of cyclohexanone were added, and the temperature was raised to 60°C while stirring. Dissolution was confirmed by visual inspection, and the liquid resin composition with a solid content of 20% by mass was obtained by cooling to 40°C. On the second component similar to the above-mentioned implementation test example 1, the above-mentioned liquid resin composition was applied by rod coating, and allowed to stand in an oven at 70°C for 30 minutes, thereby forming a phenoxy resin coating layer with a thickness of 100 μm on the surface of the second component. The weight average molecular weight of the above-mentioned coating layer is about 50,000. The epoxy equivalent is above the detection limit. No melting heat peak was detected in DSC.
[0322] (Joint body)
[0323] The same procedures as in Test Example 1 were followed, except that the first member was directly disposed on the second member having the phenoxy resin coating layer, to produce the joined bodies shown in Table 1. In order to evaluate the open time, the same procedures as above were followed, except that the phenoxy resin coating layer was formed on the surface of the second member, left to stand for 3 days, and then laminated with the first member, to produce joined bodies for open time evaluation.
[0324] <Comparative Test Example 7>
[0325] (Joint body)
[0326] The same procedures as in Test Example 1 were followed except that crystalline polyamide hot melt adhesive film NT-120 (manufactured by Nippon Matei Co., Ltd., thickness 100 μm) was used as the solid adhesive to produce joined bodies and joined bodies for open time evaluation shown in Table 1. The heat of fusion was 60 J / g.
[0327] [Shear Adhesion]
[0328] After the bonded bodies obtained in Implementation Test Examples 1 to 6 and Comparative Test Examples 1 to 7 were left to stand at a measurement temperature (23°C or 80°C) for more than 30 minutes, a tensile shear bond strength test was performed in an atmosphere of 23°C and 80°C using a tensile testing machine (universal testing machine Autograph "AG-Xplus" (manufactured by Shimadzu Corporation); load cell 10 kN, tensile speed 10 mm / min) in accordance with ISO19095 to measure the bond strength. The measurement results are shown in Table 1.
[0329] [Joining process time]
[0330] The bonding process time was determined as follows. The time from the start point to the end point was determined when the bonding agent first came into contact with one or two substrates constituting the bonded body, and when the bonded body was completed. The heating and pressing times were averaged for each value in the bonded body shown in Table 1.
[0331] [Recyclability]
[0332] After the bonded bodies shown in Table 1 were heated on a hot plate at 200° C. for 1 minute, it was determined whether they could be easily peeled off with a force of 1 N or less. If peeling was possible, it was rated as good (OK), and if not peeling was rated as unsatisfactory (NG).
[0333] [Restorability]
[0334] The first member was placed on the second member in each test piece (a layer of bonding solid remained on the surface of the first member or the second member or both) whose bonding surface was broken after the test at 23°C in the tensile shear strength test, and a bonded body was prepared in the same manner as in the above-mentioned implementation test example 1 to obtain a repaired bonded body. The shear adhesion at 23°C of the above-mentioned repaired bonded body was measured in the same manner as the above-mentioned test method, and it was considered good (OK) if it was 80% or more of the first shear adhesion, and it was considered unsuitable (NG) if it was less than 80%.
[0335] [Opening hours evaluation]
[0336] The above-mentioned tensile shear bonding strength test was performed at 23°C using a joint body for open time evaluation. If the shear bonding strength is 80% or more compared to the test piece prepared by the method of the above-mentioned implementation test example and the comparative test example, it is good (OK), and if it is less than 80%, it is set as unsuitable (NG). The so-called good open time evaluation (OK) means that the open time is long and the convenience is excellent.
[0337] surface@
[0338]
[0339] (Continued from Table 1)
[0340]
[0341] According to the present invention, a laminated body in which a first conductive layer and / or a second conductive layer (first member) and an insulating layer (second member) are firmly bonded can be manufactured with a short bonding process time and a long open time.
[0342] Industrial Availability
[0343] The present invention can be utilized in a method for producing a laminate.
[0344] Explanation of symbols
[0345] 10, 20, 30, 40, 50: laminated body, 11, 21, 31, 41, 51: first resin layer, 12, 22, 32, 42, 52: first conductive layer, 13, 23, 33, 43, 53: insulating layer, 14, 24, 34, 44, 54: second conductive layer, 15, 25, 35, 45, 55: adhesive layer, 16, 26, 36, 46, 56: second resin layer, 47: insertion portion, 57: heat sink, 100: first resin layer, 101: accommodating portion, 102A: concave portion, 102B: convex portion, 103: fixing portion, 104: opening portion, 105: first conductive layer, 106: second conductive layer.
Claims
1. A laminated body, which comprises 1st resin layer, The first conductive layer, Insulation layer, and The second conductive layer, The first resin layer has a receiving portion, The first conductive layer is arranged in the housing portion of the first resin layer. At least one of between the first conductive layer and the insulating layer and between the insulating layer and the second conductive layer is provided with an adhesive layer, the adhesive layer comprising a solid binder having an amorphous thermoplastic resin as a main component, the amorphous thermoplastic resin being at least one selected from a thermoplastic epoxy resin and a phenoxy resin, the epoxy equivalent of the amorphous thermoplastic resin being greater than or equal to 1,600 or the amorphous thermoplastic resin containing no epoxy group, The amorphous thermoplastic resin has a heat of fusion of 15 J / g or less. 2 . The laminate according to claim 1 , wherein the housing portion includes a concave portion or a concavo-convex portion. 3 . The laminate according to claim 1 , wherein the first conductive layer, the insulating layer, and the second conductive layer are arranged in the housing portion of the first resin layer. 4 . The laminate according to claim 1 , wherein an area of the housing portion of the first resin layer is equal to or larger than an area of the first conductive layer.
5. The laminate according to any one of claims 1 to 3, further comprising a second resin layer on the side of the second conductive layer opposite to the insulating layer. The adhesive layer is optionally provided between at least one of the first resin layer and the first conductive layer and between the second conductive layer and the second resin layer. 6 . The laminate according to claim 1 , wherein the first resin layer is a cured product of a resin composition containing a thermosetting resin. The laminate according to claim 6 , wherein the thermosetting resin comprises unsaturated polyester. 8 . The laminate according to claim 1 , wherein the first resin layer has a fixing portion that fixes the first conductive layer, the insulating layer, and the second conductive layer.
9. A method for manufacturing a laminate, comprising the following steps: a pre-bonding step of preparing a laminated body in which a first resin layer having a receiving portion, a first conductive layer arranged in the receiving portion of the first resin layer, an insulating layer, and a second conductive layer are sequentially arranged, and a solid bonding agent is arranged at least one between the first conductive layer and the insulating layer and between the insulating layer and the second conductive layer, wherein the solid bonding agent contains an amorphous thermoplastic resin as a main component, and the amorphous thermoplastic resin is at least one selected from a thermoplastic epoxy resin and a phenoxy resin; and a bonding step of heating and pressurizing the laminate to melt the solid bonding agent, bonding the first conductive layer to the insulating layer and / or bonding the insulating layer to the second conductive layer, The epoxy equivalent of the amorphous thermoplastic resin is 1,600 or more or the amorphous thermoplastic resin does not contain an epoxy group, The amorphous thermoplastic resin has a heat of fusion of 15 J / g or less. 10 . The method for producing a laminate according to claim 9 , wherein the heating and pressurizing are performed under the conditions of 100° C. to 400° C. and 0.01 MPa to 20 MPa. 11 . The method for producing a laminated body according to claim 9 , wherein the solid adhesive before melting has any shape selected from the group consisting of a film, a rod, particles, and a powder.
Citation Information
Patent Citations
Composite molded product and its manufacturing method
JP2021122959A
Resin composition, resin sheet, resin sheet cured product, resin sheet laminate, resin sheet laminate cured product and method for producing same, semiconductor device, and LED device
CN106103531A
Resin containing carboxyl group, photosensitive resin composition, dry film, printed wiring board, and method for producing resin containing carboxyl group
CN107250198A
Bisphenol f skeleton-containing phenoxy resin, manufacturing method therefor and resin composition using the same
JP2017171802A
Electromagnetic wave shield film and printed wiring board with electromagnetic wave shield film
JP2018166180A